2015
DOI: 10.1089/jpm.2015.0115
|View full text |Cite
|
Sign up to set email alerts
|

Time to Death after Terminal Withdrawal of Mechanical Ventilation: Specific Respiratory and Physiologic Parameters May Inform Physician Predictions

Abstract: Background: Discussions about withdrawal of life-sustaining therapies often include family members of critically ill patients. These conversations should address essential components of the dying process, including expected time to death after withdrawal. Objectives: The study objective was to aid physician communication about the dying process by identifying predictors of time to death after terminal withdrawal of mechanical ventilation. Methods: We conducted an observational analysis from a single-center, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 25 publications
(63 reference statements)
0
23
1
3
Order By: Relevance
“…( 9 ) Interestingly, our time to death after MVW was not the same as that reported in other countries. ( 21 - 24 ) Only 32% died within 24 hours, in contrast to 90% in the USA ( 23 ) (possibly owing to a different case mix of palliative extubation patients), where the withdrawal of life support in the anticipation of death for patients with refractory shock or respiratory failure is more common.…”
Section: Discussionmentioning
confidence: 99%
“…( 9 ) Interestingly, our time to death after MVW was not the same as that reported in other countries. ( 21 - 24 ) Only 32% died within 24 hours, in contrast to 90% in the USA ( 23 ) (possibly owing to a different case mix of palliative extubation patients), where the withdrawal of life support in the anticipation of death for patients with refractory shock or respiratory failure is more common.…”
Section: Discussionmentioning
confidence: 99%
“…Robert et al 39 reported that death occurred more rapidly in patients not experiencing discomfort during withdrawal of mechanical ventilation, but there was no association between doses of sedation and analgesia and the shortening or delay of death. In the study by Mazer et al, 38 higher doses of opioids given the hour before death after terminal extubation correlated with statistically significant longer time to death, whereas Long et al 12 reported that higher doses of opioids and benzodiazepines were associated with shorter time to death. Three studies reported on the factors affecting the decision for terminal withdrawal or terminal extubation.…”
Section: Time To Death and Predictorsmentioning
confidence: 93%
“…A recent observational study from France suggests that either approach may have the same psychological impact to patients’ relatives, despite terminal extubation being associated with greater risk of airway obstruction and higher frequency of gasping. 7 In addition, in a study by Long et al, 12 it was found that time to death was quicker following terminal extubation as opposed to other practices (i.e. terminal weaning) and yet in the review by Hinkle et al 11 it was reported that a ‘longer period of withdrawal increased family satisfaction’ (pp.…”
Section: Introductionmentioning
confidence: 99%
“…Contrariamente a nuestros hallazgos, la extubación terminal es una práctica frecuente en diversos sitios. El estudio desarrollado por Long y colaboradores, analizando 330 pacientes fallecidos luego de una decisión de LTSV, mostró que el 74% de los pacientes eran extubados previo a su fallecimiento (20) . Por su parte, Grestel y colaboradores encontraron que la extubación terminal se relaciona con un incremento de la satisfacción familiar (21) .…”
Section: Discussionunclassified